Fossil penguin beaks from the Eocene of Antarctica: new materials from La Meseta Formation - Haidr, Nadia Soledad (2017)
New materials coming from different levels of the La Meseta and Submeseta formations, including the most complete beak of a penguin (MLP 14-XI-27-27) from Antarctica, are described here. A new morpho-geometric approach, based on Principal Component Analysis, and Elliptic Fourier Analysis, was performed to analyze the articular area of the mandibles and maxilar remains, a skeletal correlate of dietary habits. As a result, we can infer that most of the penguins analyzed belong to the piscivorous morphotype. This corroborates the abundance of piscivores in the Eocene of Antarctica and provides more information regarding the morphological configurations of the predominantly crustacivore penguins.